Konstelasi kekuatan partai politik dalam pemilu serentak tahun 2019 di Kabupaten Pemalang - Unggul Sugi Harto (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2022)
The general election is a contestation involving political parties and individuals in a democracy, where various processes and details follow. The result of the election is a number of vote which are then converted into seats in the legislature or the electability of the elite. These two results the become materials that are constantly being studied and analyzed, of course with various basid research objectives. The number of good votes obtained by political parties, legislative candidates, regional elite candidates to the president is rich in meaning and shows a variety of studies. Figures obtained by political parties both of the national level, especially at the regional level, have variouse aspect, such as strength of the party the power of the political machine or the level of competition in the region. These meanings are quite reasonable because the number of party votes, especially in the regoins, shows the dynamics closest to the vasiouse phenomena of the competition between political parties themselves. The study of the vote acquisition of political parties in regions, especially the districts, is a micro study developed by the electoral district  (Daerah Pemilihan/Dapil). This constituency is the main point for cq’s vote. Seats in the regional legislature as well as evidence of the strength of political parties in the electoral district. Many variations appear when reading the vote count, of course, because each electoral district has has certain characteristics that tend to be relatively different. This study focuse on the vote acquisition of political parties in the electoral district in Pemalang Regency, Central Java. Pemalang Regency is located in the North West part of Central Java, and is crossed by national arterial road known as The Pantura (Pantai Utara Jawa). The large base political parties is PDI P, PKB, Gerindra, P Golkar, PPP and PKS, a political party strength which is also manifesd in the national political map. The vote gain of political parties are the looked at per eletoral district and then compared between parties, and the result is a vairety of variations as a result of the local poltical prosesses of each different electoral district.